Effect of External Ventricular Drain Care Guidelines on Nursing Practice and Complications among Patients with Post-Traumatic Hydrocephalus - Hina Aslam, Muhammad Afzal, Hajra Sarwar, Sadia Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: External Ventricular Drain (EVD) care is considered as an advanced specialized nursing skill for neurological patients. EVD care guidelines plays a vital role in improving nurses’ practices regarding care of patients with EVD. The complications associated with EVD are strongly linked with nursing care as well as their level of practices. Unfortunately, in clinical settings most of nurses have incompetent EVD care practices. So, there is a dire need to adopt EVD care guidelines to improve their practices regarding EVD care. Objective: To assess the effect of external ventricular drain care guidelines on nursing practice and complications among patients with post traumatic hydrocephalus. Methodology: A quasi experimental study included 120 registered nurses and 80 patients selected with a purposive sampling technique. A 10 weeks educational intervention consists of PowerPoint lectures on EVD care guidelines of American Association of Neuroscience Nurses (AANN), audio visual demonstration (AVD) and hands on workshop practice sessions were given by the expert of relevant field to registered nurses on caring of patients with (EVD). Data on nurses’ practices and complications among patients were collected two times before and after the intervention via validated tools. Results: The study revealed a significant (p<0.001) change in nurses’ practices and patients’ complications after External ventricular drain (EVD) care guidelines implementation. The practices had been competent as 79 (65.8%) from 8(6.7%). The complication of meningitis in pre-guidelines implementation was 30 (75%) and post-guidelines implementation it was 13(32.5%).The kinking of tube was reduced from 4 (10.0%) to 3(7.5%). After guidelines implementation the rest of complications of EVD were also reduced among patients. Conclusion: External ventricular drain (EVD) care guidelines of American Association of Neuroscience Nurses (AANN) significantly improve registered nurses practices which ultimately reduced the complications of EVD among patients.